2018
DOI: 10.1007/s12031-018-1206-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker and Drug Target Discovery Using Quantitative Proteomics Post-Intracerebral Hemorrhage Stroke in the Rat Brain

Abstract: The pathological mechanisms of acute intracerebral hemorrhage (ICH) remain unknown and unverified. In the present study, we used quantitative proteomics to elucidate the pathological mechanisms and to identify novel biomarker and therapeutic target candidates via tissue proteome in a rat model of acute ICH. Rats were experimentally induced with ICH (n = 6) or Sham (n = 6), and their brain tissue was obtained by 24 h. The TMT-LC–MS/MS-based proteomics approach was used to quantify the differential proteomes acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Although albumin has a variety of neuroprotective effects on ICH-induced injury, however, the potential molecular mechanisms involved with the activation of ERK by albumin have not been fully investigated. Our previous quantitative proteomics study [ 23 ] showed that the ERK1 and ERK2 cascades were the top two biological processes after ICH and that the albumin and ERK1/2 signaling pathways were the top protein-protein interaction networks. Recently, some studies showed that there was an important link between albumin and the mitogen-activated protein kinase (MAPK) extracellular signal-regulated kinase, ERK1/ERK2 in kidney disease, and ERK1/2 signaling pathway was the downstream signal activated by albumin therapy [ 24 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although albumin has a variety of neuroprotective effects on ICH-induced injury, however, the potential molecular mechanisms involved with the activation of ERK by albumin have not been fully investigated. Our previous quantitative proteomics study [ 23 ] showed that the ERK1 and ERK2 cascades were the top two biological processes after ICH and that the albumin and ERK1/2 signaling pathways were the top protein-protein interaction networks. Recently, some studies showed that there was an important link between albumin and the mitogen-activated protein kinase (MAPK) extracellular signal-regulated kinase, ERK1/ERK2 in kidney disease, and ERK1/2 signaling pathway was the downstream signal activated by albumin therapy [ 24 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that human serum albumin treatment had neuroprotective effects on focal and global cerebral ischemia [ 18 , 19 ], subarachnoid hemorrhage [ 20 , 21 ], and ICH [ 22 ]. Our previous quantitative proteomics study showed that albumin increased after ICH [ 23 ], but the specific mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomics is the large-scale analysis of proteins, including post-translational modifications and protein interactions, so as to reveal the function of proteins. Proteomics has been used in the screening of vaccines, clinical drug development, the prediction of prognosis, and to guide treatment approaches (7). Metabolomics is the qualitative and quantitative analysis of all low molecular weight metabolites in the biological system at a specific time and under specific conditions, and describes the responses of endogenous metabolites to internal and external changes.…”
Section: In Addition the Activation Of Inflammatory Responsesmentioning
confidence: 99%
“…Unfortunately, effective pharmaceutical approaches for ICH are lacking at present [11]. One of the challenges in drug development is the poor oral bioavailability and brain accumulation [12,13].To resolve these puzzles, extensive research efforts have been pursued in the quest for novel compounds from herbal medicines [14].…”
Section: Introductionmentioning
confidence: 99%